Kebijakan Bebas Visa di Tengah Pandemic Covid 19 dan Implikasinya Bagi Stabilitas Nasional Indonesia Berdasarkan Hukum Keimigrasian - Fitrah, Jihan; Peilouw, Johanis Steny Franco; Tuhulele, Popi (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The government is currently trying to reduce the spread of COVID-19 in various ways. The issuance of the Circular of the COVID-19 Handling Task Force is an effort to deal with the COVID-19 pandemic. Not only does it regulate the lives of citizens in the country, the government has also decided to close the door for foreigners from abroad to enter. The ban on the entry of foreigners has even been increased since January 1 2021 All foreigners are prohibited from entering Indonesian territory, except for some groups who are excluded such as foreigners with Limited Stay Permits (ITAS), Permanent Stay Permits (ITAP), and Service and Diplomatic Stay Permits.Purposes of the Research: To find out about how the visa-free policy is regulated in the midst of the Covid 19 pandemic based on immigration law and what are the implications for national stability based on the principle of selective policy.Methods of the Research: The research method used is normative juridical. by using (state approach) and (statute approach). And sources of primary, secondary and tertiary legal materials as well as literature studies, then analyzed qualitatively.Results of the Research: The results of this study indicate that the visa-free policy has so far been stopped temporarily until the Covid 19 pandemic is declared over by the government. We can see this in the current Minister of Law and Human Rights, namely Minister of Law and Human Rights Number 34 of 2021 concerning Granting Visas and Immigration Stay Permits during the Handling Period of the Spread of Corona Virus Disease 2019 and National Economic Recovery. Over time, on April 6, the Ministry of Law and Human Rights, in this case the Director General of Immigration, issued a new policy regarding granting Free Visit Visas for special tours and Visit Visas on Arrival/VoA specifically for tourism which are listed in the Director General of Immigration Circular Letter Number IMI-0603.GR.01.01 2022 regarding Immigration Facilities in the Context of Supporting Sustainable Tourism During the 2019 Corona Virus Disease Pandemic. In the circular letter, foreigners who are allowed to enter using visa-free are 9 ASEAN countries. The nine ASEAN countries are Brunei Darussalam, the Philippines, Cambodia, Laos, Malaysia, Myanmar, Singapore, Thailand and Vietnam.